Przyczyny kryzysu teorii prawa - Morawski, Lech (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In my opinion contemporary analytic jurisprudence is in deep crisis. This thesis refers mainlyto the analysis of law in terms of formal logic, which turned out to be a useless and fruitless research instrument of the legal problems. The best years are also behind analytic philosophy in the style of language philosophy. Contemporary jurisprudence deals more and more with the constitutional, political or economic problems or attempts to combine these approaches see Dworkin or Law and Economics. However, this turnabout causes the politicization and commercialization of contemporary jurisprudence and creates new challenges and threats to the legal sciences which in turn may lead to the moral crisis of scientific ethos. I devoted my paper to the analysis of this problem.
Keywords: teoria prawa; kryzys